2020
DOI: 10.1176/appi.focus.20190028
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities to Meet the Mental Health Needs of Underserved and Disenfranchised Populations in the United States

Abstract: This article investigates the gap in access to and quality of mental health care in the United States. This work first discusses how minority populations are most affected by the treatment gap. It summarizes recent literature on the topic for better understanding the needs of psychiatrically underserved and disenfranchised populations and the causes of mental health disparities. It reviews some of the barriers to behavioral health care, including lack of insurance coverage, lack of community-based intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 78 publications
1
81
0
Order By: Relevance
“…A review of severity and mortality risks at a presentation by household income as a SDoH indicator shows consistently higher moderate risks among lower income and many minority populations between 2012-2014 and 2016-2017. Such findings are consistent with other studies that have found higher stressors among low-income and minority communities [ 16 , 22 - 25 ]. These findings call for a re-evaluation of public policy on social and economic inequalities and support models focusing on minority populations to mitigate poor SDoH.…”
Section: Discussionsupporting
confidence: 93%
“…A review of severity and mortality risks at a presentation by household income as a SDoH indicator shows consistently higher moderate risks among lower income and many minority populations between 2012-2014 and 2016-2017. Such findings are consistent with other studies that have found higher stressors among low-income and minority communities [ 16 , 22 - 25 ]. These findings call for a re-evaluation of public policy on social and economic inequalities and support models focusing on minority populations to mitigate poor SDoH.…”
Section: Discussionsupporting
confidence: 93%
“…This brought the total down to 136 articles for full-text review. Following the full-text review, articles that duplicated the insights already gained were excluded, leaving a final total of 53 articles for inclusion in the review across the six medical specialties [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. Table 2 (below) summarizes the key themes and insights that emerged from the narrative review and synt...…”
Section: Resultsmentioning
confidence: 99%
“…[65,75] Concurrently, each "higher-using" specialty is replete with examples of initiatives from individual providers, to improve patient experience, enable disease management, reduce costs, and promote population health, which reveals an entrepreneurial and patient-centric culture as opposed to a reimbursement-oriented, provider-centric culture. [62,72,88] In other words, in the "higher-using" specialties all three levers of the Triple Aim framework appear to have been in motion, serving as motivators for telehealth use at the provider (micro) and organizational (meso) levels. By contrast, all three motivators appear to have been missing among the "lower-using" specialties.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in telepsychiatry, each state has its own licensing boards that establish practice jurisdictions for providers licensed in the state, and some have speci c regulations. [72,90] Similarly, the legal environment for teleradiology in the US is a limiting factor. For comprehensive services with nal reading, radiologists need to be licensed in the remote institution's state, credentialed in the institution and insured for medico-legal liability.…”
Section: Macro: Legal and Ethical Factorsmentioning
confidence: 99%